Технологія формування педагогічної майстерності у майбутніх тренерів - Юшко, Олексій Володимирович; Борейко, Наталя Юріївна; Азаренкова, Любов Леонідівна (Полтавський національний педагогічний університет ім. В. Г. Короленка, 2018)
У статті проаналізовано поняття "педагогічна майстерність" та визначено складники педагогічної майстерності тренера. Розкрито особливості формування педагогічної майстерності майбутніх тренерів у НТУ "ХПІ". Розроблені критерії та визначено рівень сформованості педагогічної майстерності у студентів 1-4 курсів. Досліджено вплив навчальних дисциплін на сформованість компонентів педагогічної майстерності у майбутніх тренерів.

The article analyzes the concept of "pedagogical skill" and defines the components of pedagogical skills of the coach. The peculiarities of the formation of pedagogical skills of future trainers in NTU "KhPI" are revealed. The criteria have been developed and the level of formation among the students of the 1st and 4th courses has been determined. The influence of educational disciplines on the formation of components of the pedagogical skills of future coaches has been studied. The results of the study showed that the mastering of the theoretical material of the academic disciplines of the professional block of the curriculum of the specialty "Physical Culture and Sport" and the formation of practical skills of sports and professional development makes it possible to form a high level of pedagogical skills. According to the research, the introduction of technology significantly increased the indicators of the formation of components of pedagogical skill students experimental group. Students became more active, showed creativity in practical classes, performed self-analysis of their results.
Technology of formation of teaching skills of future coaches
Keywords: студенти; педагогічна майстерність; педагогічні технології; тренер; навчальна дисципліна; students; pedagogical skill; pedagogical technology; trainer; academic discipline